Clinical course of pituitary function and image in IgG4-related hypophysitis - Anno, Takatoshi (Endocrinol Diabetes Metab Case Rep, 2017)
A 76-year-old man had a hypopituitarism including adrenal insufficiency, hypogonadism and hypothyroidism. Based on various findings including the swelling of the pituitary gland, increase of serum IgG4 level and abundant IgG4-positive plasma cell infiltration in immunostaining of the pituitary gland, we diagnosed this subject as IgG4-related hypophysitis. In general, a high-dose glucocorticoid treatment is effective for IgG4-related disease. His clinical symptom, laboratory data and adrenal insufficiency were almost improved without any therapy. The serum IgG4 level was decreased and pituitary size was normalized with hydrocortisone as physiological replacement. This case report provides the possibility that IgG4 level is decreased spontaneously or with physiological dose of glucocorticoid therapy. LEARNING POINTS: We performed the pituitary gland biopsy and histochemical examination glucocorticoid therapy in a subject with IgG4-related hypophysitis. This case report provides the possibility that IgG4 level is decreased spontaneously or with a physiological dose of glucocorticoid therapy. We reported the clinical course of IgG4-related hypophysitis without a high-dose glucocorticoid treatment, although there were a few reports about the retrospective examination. Although the patient had still higher IgG4 level compared to normal range, his clinical symptom disappeared and his laboratory data were improved. We should keep in mind the possibility of IgG4-related hypophysitis when we examine one of the uncertain causes of a hypopituitarism including adrenal insufficiency, hypogonadism and hypothyroidism.